1986
DOI: 10.1073/pnas.83.15.5397
|View full text |Cite
|
Sign up to set email alerts
|

Design and biological activity of analogs of growth hormone releasing factor with potential amphiphilic helical carboxyl termini.

Abstract: A 29-amino acid analog of growth hormone releasing factor (GHRF) was designed in which the sequence of the first six amino acids at the amino terminus was maintained while the postulated amphiphilic helical structure in the remainder of the molecule was optimized. The amino acid sequence of the analog differed from that of the first 29 residues of human GHRF by 13 residues. The peptide was synthesized by the solid-phase procedure in amide and free acid forms, both of which were tested for biological activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The amphiphilic regions may induce p helicity to bind with the surface. Studies of model peptides suggest that such arrangements may occur in b-endorphin, 57-59 melittin, growth hormone releasing factor, 60,61 and in analogues of a vasoactive intestinal peptide. 62 In a designed sequence, i,i15 spacing of interacting residues could be used to encourage such a structure.…”
Section: Discussionmentioning
confidence: 99%
“…The amphiphilic regions may induce p helicity to bind with the surface. Studies of model peptides suggest that such arrangements may occur in b-endorphin, 57-59 melittin, growth hormone releasing factor, 60,61 and in analogues of a vasoactive intestinal peptide. 62 In a designed sequence, i,i15 spacing of interacting residues could be used to encourage such a structure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that GHRF binds to GHRHR and up-regulates the expression of the GH gene in healthy human and rat pituitary cells (Bloch et al 1983; Montero et al 2000; Thorner et al 1983) with an optimal range of 1–3 μg/kg body weight in vivo and 0.1–10 nM in vitro (Thorner et al 1983; Velicelebi et al 1986). Serum levels of PRL and LH were not increased after administration of human GHRF at 1 μg/kg body weight (Thorner et al 1983).…”
Section: Resultsmentioning
confidence: 99%
“…Proteins are built from secondary structure units, including the α helix and the β strand 60 . This gave rise to the idea that such secondary structural elements might serve as interchangeable parts to support protein design 61 .…”
Section: Seeking Interchangeable Parts: Proteinsmentioning
confidence: 99%